First Law Analysis of a Two-stage Ejector-vapor Compression Refrigeration Cycle working with R404A - Feiza Memet (Analele Universităţii "Eftimie Murgu" Reşiţa: Fascicola I, Inginerie, 2011)
The traditional two-stage vapor compression refrigeration cycle might be replaced by a two-stage ejector-vapor compression refrigeration cycle if it is aimed the decrease of irreversibility during expansion. In this respect, the expansion valve is changed with an ejector. The performance improvement is searched in the case of choosing R404A as a refrigerant. Using the ejector as an expansion device ensures a higher value for COP compared to the traditional case. On the basis of the ejector approach it possible to identify the highest COP value for a given condensation temperature, when the evaporation temperature varies.